The Possibility of Using Endophytic Micromycetes for Increasing Plant Metal Resistance - Bukharina, Irina; Islamova, Nadezhda (KnE Life Sciences, 2022)
The aim of this research was to study the effect of inoculation with the Cylindrocarpon magnusianum endotrophic micromycete on the physiological and biochemical parameters of tomato test plants under the action of heavy metal salts. The plants were inoculated with the fungus culture (control population) and populations of this fungus preliminarily adapted to the action of the stress factor. Then, inoculated plants were grown under control conditions and on substrates with different concentrations of heavy metal salts (zinc, copper, lead and chromium). After the plants were inoculated with the control population of the C. magnusianum fungus, a stimulating effect increasing the plants’ resistance to the action of the heavy metal salts was not detected. When the plants were inoculated with adapted populations of the C. magnusianum fungus, adaptive reactions of the plants associated with the content of photosynthetic pigments in the leaves and the formation of plant biomass were significantly manifested. Under these conditions, a more intense development of fungal infection in plant roots was observed in contrast to the use of the control fungal population. These findings therefore demonstrated an effective partnership between the C. magnusianum fungus and the root system of plants under extreme conditions for plant life. Keywords: Cylindrocarpon magnusianum, micromycetes, heavy metals, inoculation, biochemical indicators